1997
DOI: 10.1074/jbc.272.30.18855
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Porcine Pepsin

Abstract: The S 1 substrate specificity of porcine pepsin has been altered to resemble that of fungal aspartic proteinase with preference for a basic amino acid residue in P 1 by site directed mutagenesis. On the basis of primary and tertiary structures of aspartic proteinases, the active site-flap mutants of porcine pepsin were constructed, which involved the replacement of Thr-77 by Asp (T77D), the insertion of Ser between Gly-78 and Ser-79 (G78(S)S79), and the double mutation (T77D/G78(S)S79). The specificities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Since cleavage at the mutated ϳVal 29 -Phe 30 ϳ bond was no longer an option, it was found by amino acid analysis that processing had taken place at the adjacent ϳPhe 30 *Lys 31 ϳ bond (data not shown). Similarly, peptides 12 and 13 (Table II) were digested after 72 h incubation with proteinase A at a molar ratio of 10:1, as were peptides 18,19,20, and 26 of the peptides listed in Table IV. Thus, in addition to the L19A mutant (peptide 27) as described above, the other peptides (7,8,12,13,14 (Table II), 18, 19, 20, and 26 (Table IV)) which were not effective as inhibitors of proteinase A, served instead as substrates for the enzyme.…”
Section: Ntd Qqkvs Eifqs Skeka Qgdak Vvsda Fkkmentioning
confidence: 99%
“…Since cleavage at the mutated ϳVal 29 -Phe 30 ϳ bond was no longer an option, it was found by amino acid analysis that processing had taken place at the adjacent ϳPhe 30 *Lys 31 ϳ bond (data not shown). Similarly, peptides 12 and 13 (Table II) were digested after 72 h incubation with proteinase A at a molar ratio of 10:1, as were peptides 18,19,20, and 26 of the peptides listed in Table IV. Thus, in addition to the L19A mutant (peptide 27) as described above, the other peptides (7,8,12,13,14 (Table II), 18, 19, 20, and 26 (Table IV)) which were not effective as inhibitors of proteinase A, served instead as substrates for the enzyme.…”
Section: Ntd Qqkvs Eifqs Skeka Qgdak Vvsda Fkkmentioning
confidence: 99%
“…1 green boxes) bind to the catalytic aspartates (Fig. 1 black boxes “+”) [1], [26], [27], [28] In an acidic pH environment acidic residues in the enzyme moiety become protonated disrupting electrostatic interactions with the prosegment (which has a basic character), releasing the prosegment for proteolytic cleavage and enzyme activation [3], [29], [30]. In fish pepsinogens a deletion of several residues in the prosegment is observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In all mammalian proteins that favour a hydrophobic P1 residue, Asp76 is substituted by Thr or Ser and Ser78 is deleted. It has been suggested that Asp76 interacts with P1 lysine, contributing to the transition-state stabilization, and that Ser78 is important for the proper orientation of the side chain of Asp76 (Shintani et al, 1997). The hydrogen bond between Asp76 and Ser78 is indeed present in molecule A but not in B.…”
Section: Comparison Of the Two Aspergillopepsin Moleculesmentioning
confidence: 99%
“…Prediction of the binding preferences from the amino-acid sequence is dif®cult because the speci®city is determined by extensive interactions occurring at multiple subsites and the shape of each subsite is delineated by the structures of the¯exible loops as well as the individual aminoacid residues in the loops (Dunn & Hung, 2000). Site-directed mutagenesis showed that a single mutation at the binding site alters the substrate speci®city (Scarborough & Dunn, 1994;Shintani et al, 1997).…”
Section: Introductionmentioning
confidence: 99%